(untitled) (International Journal of Sustainable Energy and Environmental Research, 2014)
This article provides hydraulic and thermal properties of soils and rocks. The impact of groundwater flow on the estimation of soil/rock thermal conductivity from test data was also examined. The purpose of this study, however, is to examine the means of reduction of energy consumption in buildings, identify GSHPs as an environmental friendly technology able to provide efficient utilisation of energy in the buildings sector, promote using GSHPs applications as an optimum means of heating and cooling, and to present typical applications and recent advances of the DX GSHPs.